2019
DOI: 10.1002/admt.201900669
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond Pulsed Electric Field Lab‐on‐Chip Integrated in Super‐Resolution Microscope for Cytoskeleton Imaging

Abstract: Nanosecond pulsed electric field offers novel opportunities in bionanotechnology and biomedicine enabling ultrafast physical control of membrane, and protein‐based processes for the development of novel bionanomaterials and biomedical theranostic methods. However, the mechanisms of nanosecond pulsed electric field action at the nano‐ and molecular scale are not fully understood due to lack of appropriate research tools. In order to overcome this challenge, a technological platform for the exploration of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…In this study, MT disruption was temporally associated with loss of mitochondrial membrane potential, and EB3 changes were found to be independent of calcium and cell swelling, suggesting a direct breakdown of interphase MTs. A subsequent study by Havelka et al using 11 ns pulses (~67.5 kV/cm, 4000 p) also showed significant changes to EB3 dynamics in rat basophilic (RBL-2H3) cells [82].…”
Section: Microtubules Disruptionmentioning
confidence: 80%
See 1 more Smart Citation
“…In this study, MT disruption was temporally associated with loss of mitochondrial membrane potential, and EB3 changes were found to be independent of calcium and cell swelling, suggesting a direct breakdown of interphase MTs. A subsequent study by Havelka et al using 11 ns pulses (~67.5 kV/cm, 4000 p) also showed significant changes to EB3 dynamics in rat basophilic (RBL-2H3) cells [82].…”
Section: Microtubules Disruptionmentioning
confidence: 80%
“…Some cancer cells show altered γ-tubulin levels, which modulate MT nucleation. Thus, modulating MT nucleation by PEFs may open new therapeutic opportunities [82]. Electromechanical models of mitotic spindle vibration by Havelka et al suggest nsPEF-driven electro-acoustic behavior of mitotic spindles may have a disrupting effect on kinetochore-microtubule binding or chromatid separation with implications for cancer treatment [186].…”
Section: Cytoskeletal Targets For Improved Pef Therapiesmentioning
confidence: 99%
“…However, in our case, the major mechanism is the torque action on the tubulin dipole, which is a few-fold higher than in most other proteins [46] . Furthermore, in contrast to the intense microsecond and millisecond electric pulses that have been explored in bio-electrochemistry for several decades [76] , the nanosecond electric pulses represent a much more recent area of research [77] and offer several distinct new features [17] . The feature with the strongest impact on the chemistry is that in the nanosecond pulse regime an electric field strength of a few tens of MV/m (approaching the strength of local molecular fields [78] , [79] ) can be attained throughout the volume exposed to the electric field without appreciable heating [17] , [3] .…”
Section: Discussionmentioning
confidence: 99%
“…The effects of short (nanosecond range) intense electric pulses on MTs have been demonstrated in cells: A MT network was disrupted, either immediately [16] or with some delay [17] , after electric pulses were applied. A recent study demonstrated the possibility to remodel the MT cytoskeleton in cells without a complete de-polymerization phase [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Research of self-propelling colloids is at a more fundamental stage compared to assembly, yet synthetic motile microparticles have outstanding potential in drug delivery, bioremediation, and also catalysis. In particular, we expect major advances in controlling motion within complex environments that are more realistic for applications such as in biomedical devices and environmental remediation. These include porous media, suspensions of macromolecules, and cellular environments. Further key research directions are distilled as follows: understand the role of thermodynamics vs kinetics in the assemblies formed by weak, competing field-induced interactions deconvolute the respective roles of particle shape, surface chemistry, and dispersing medium in field-induced colloidal phenomena find new methodologies to override stochastic Brownian forces and achieve organized active motion at the submicron scale by coupling multiple electromagnetic fields develop new field-induced colloidal platforms that respond to environmental cues and spontaneously self-regulate their structural and temporal characteristics expand the domain of fundamental active matter research to advanced materials capable of performing sophisticated functions such as energy transfer and mechanical work at the nanoscale …”
Section: Discussionmentioning
confidence: 99%